TINJAUAN YAYASAN PENDIDIKAN DITINJAU DARI SUDUT UNDANG-UNDANG TENTANG YAYASAN - Mochamad Novel (LPPM Universitas Bina Bangsa, 2022)
This research focuses on the implementation of foundation based on Law No. 28 Year 2004 about Foundation. Foundation has a contribution to implement a specific object such a social, humanity, and religiousity, included the educational foundation. This research is using normative and sociological type of research, which means this study conceptualized as what is written in the legislation and its relation with the actual practice. Analysis of materials research is using qualitative methods in order to draw conclutions using deductive methods. This research shows that the foundation as a social institution can not be said as a business entity